2021
DOI: 10.3389/fsurg.2021.667154
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Combined Preoperative Carcinoembryonic Antigen and Prognostic Nutritional Index in Patients With Stage II–III Colon Cancer

Abstract: Background: Tumor status can affect patient prognosis. Prognostic nutritional index (PNI), as a nutritional indicator, is closely related to the prognosis of cancer. However, few studies have examined the combined prognostic value of CEA and PNI in patients. This study investigated the relationship between CEA/PNI and prognosis of colon cancer patients.Methods: A total of 513 patients with stage II–III colon cancer who underwent curative resection at two medical centers from 2009 to 2019 were included. Clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For example, Uejima et al included 135 stage II patients and found that a combination of PNI and CEA exhibited good prognostic efficacy, but the 5-year DFS rates in the CEA low /PNI high , CEA high /PNI high and CEA low /PNI low groups were 100%, 100% and 97.4%, respectively, making it difficult to distinguish the survival differences [ 43 ]. Similarly, Xu et al enrolled 513 stage II–III patients and reported that PNI and CEA represent a superior combination, but the 1- and 3-year OS rates in the aforementioned patient subgroups were undistinguishable [ 44 ]. Taking into account these results, it was suggested that an additional indicator that was more reliable than CEA was needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Uejima et al included 135 stage II patients and found that a combination of PNI and CEA exhibited good prognostic efficacy, but the 5-year DFS rates in the CEA low /PNI high , CEA high /PNI high and CEA low /PNI low groups were 100%, 100% and 97.4%, respectively, making it difficult to distinguish the survival differences [ 43 ]. Similarly, Xu et al enrolled 513 stage II–III patients and reported that PNI and CEA represent a superior combination, but the 1- and 3-year OS rates in the aforementioned patient subgroups were undistinguishable [ 44 ]. Taking into account these results, it was suggested that an additional indicator that was more reliable than CEA was needed.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the 3-year OS rates in the PDS 0, 1 and 2 subgroups were 95.35%, 75.51% and 59.62%, respectively (P < 0.001), and could be effectively separated. However, when patients were divided into 4 subgroups (PNI high /DD low , PNI high /DD high , PNI low /DD low and PNI low /DD high ) as noted in previous studies (only those stage II–III) [ 43 , 44 ], the 3-year OS rates were 95.35%, 80.95%, 71.43%, and 58.82%, respectively (P = 0.001, data not shown), and it was also difficult to separate the survival differences among the subgroups except for the comparisons between the PNI high /DD low and PNI low /DD high as well as the PNI high /DD high and PNI low /DD high subgroups. These results were partly consistent with previous studies [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Comorbidity indices, such as the Recursive Partitioning Analysis (RPA) class, the 5-item modified frailty index (MFI-5) and prognostic nutritional index (PNI), have been increasingly utilized in both oncological and neurosurgical practices to represent a comprehensive comorbidity status that aims to improve the prediction of prognosis. [14][15][16][17][18] For instance, a higher MFI-5 score predicted worse early outcomes and 30-day readmissions following CRC surgeries. 19,20 The PNI has been shown to be a prognostic indicator for survival in patients with BM from non-small cell lung cancer and glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the incidence of CRC ranks fourth among all malignancies and the mortality ranks fifth (3). Advances in treatment methods such as surgery, chemoradiotherapy, immunotherapy, and targeted therapy have improved the prognosis of CRC; however, many CRC patients experience distant metastasis or local recurrence after receiving anticancer therapy (4)(5)(6)(7). The survival rate of CRC patients with recurrence and metastasis can be reduced to 5-10% (8,9).…”
Section: Introductionmentioning
confidence: 99%